2010
DOI: 10.1101/gad.1940210
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of leukocytes triggered by acute DNA damage promotes lymphoma formation

Abstract: Apoptosis triggered by p53 upon DNA damage secures removal of cells with compromised genomes, and is thought to prevent tumorigenesis. In contrast, we provide evidence that p53-induced apoptosis can actively drive tumor formation. Mice defective in p53-induced apoptosis due to loss of its proapoptotic target gene, puma, resist γ-irradiation (IR)-induced lymphomagenesis. In wild-type animals, repeated irradiation injury-induced expansion of hematopoietic stem/progenitor cells (HSCs) leads to lymphoma formation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
113
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 28 publications
13
113
0
Order By: Relevance
“…9 Previously, it has been shown that the absence of PUMA (or overexpression of BCL-2) could greatly delay or even prevent development of γ-radiation-induced thymic lymphoma, a malignancy that is, like MDS, also derived from bone marrow HSCs. 31,37 We previously showed that overexpression of BCL-2 with consequent blocking of apoptosis could have a similar effect in the presence of an established MDS-initiating cell. 16 The effects seen with loss of PUMA extend our previous work by identifying the BH3-only protein that is essential for initiating apoptosis in this setting.…”
Section: Discussionmentioning
confidence: 97%
“…9 Previously, it has been shown that the absence of PUMA (or overexpression of BCL-2) could greatly delay or even prevent development of γ-radiation-induced thymic lymphoma, a malignancy that is, like MDS, also derived from bone marrow HSCs. 31,37 We previously showed that overexpression of BCL-2 with consequent blocking of apoptosis could have a similar effect in the presence of an established MDS-initiating cell. 16 The effects seen with loss of PUMA extend our previous work by identifying the BH3-only protein that is essential for initiating apoptosis in this setting.…”
Section: Discussionmentioning
confidence: 97%
“…The BH3-only protein PUMA is essential for p53-mediated apoptosis in thymocytes and its loss enhances myc-induced lymphomagenesis [48][49][50][51] . Counter-intuitively, loss of PUMA prevents rather than promotes thymic lymphoma following irradiation 52,53 . Similarly, in a carcinogen-induced liver cancer model, deletion of PUMA or overexpression of anti-apoptotic BCL-2 protein also delays tumour development 54,55 .…”
Section: Apoptosis Cell Competition and Cancermentioning
confidence: 99%
“…55 Remarkably, loss of PUMA completely abrogated γ-radiation-induced thymic lymphoma development. 111,112 This striking finding could be attributed to the profound resistance of PUMA-deficient white blood cells to DNA damage-induced apoptosis. The persistence of these cells obviated the need for mobilisation and burst of proliferation of haematopoietic stem/ progenitor cells that would normally occur to repopulate the depleted haematopoietic system, 111,112 a process that appears to be required for lymphoma development in this model.…”
Section: Mcl1mentioning
confidence: 99%
“…111,112 This striking finding could be attributed to the profound resistance of PUMA-deficient white blood cells to DNA damage-induced apoptosis. The persistence of these cells obviated the need for mobilisation and burst of proliferation of haematopoietic stem/ progenitor cells that would normally occur to repopulate the depleted haematopoietic system, 111,112 a process that appears to be required for lymphoma development in this model. 109 These observations suggest that accumulation of DNA lesions, some of them potentially oncogenic, is not sufficient to induce tumour formation unless it is also accompanied by a drive for proliferative expansion of the mutation bearing leukaemia/lymphoma-initiating cells.…”
Section: Mcl1mentioning
confidence: 99%